The Position of Joint Property After the Dissolution of Marriage According to Law No. 1 of 1974 and the Compilation of Islamic Law - Rania, Rania; Sudiro, Ahmad (Universitas Islam Sultan Agung, 2024)
Marriage is not only a personal or private matter, but has a social dimension that requires government involvement. According to Islamic law, marriage is an act of worship, so the protection of Muslims in carrying out worship through the implementation of marriage is contained in Article 28e paragraph 1 of the 1945 Constitution. Law No. 1 of 1974 concerning Marriage is a manifestation of the Indonesian state as a state of law The Marriage Law is contained in Article 2, namely, marriage is valid, if it is carried out according to the laws of each religion. In establishing legal policies in Indonesia, the government has made Islamic law part of national law through the Compilation of Islamic Law (KHI) In this case, Muslims in Indonesia use KHI as a legal basis in cases of marriage breakup, including the division of property in marriage. The legal research method used in this research is research normative juridical which is research conducted or aimed only at written regulations with the nature of descriptive analysis research which is a method that functions to describe or provide an overview of the object under study. The data source used is secondary data with analysis quantitative data The position of joint property in marriage according to fiqh is not regulated, because in the Qur'an, hadith or fiqh books there is no discussion of joint property. property. The study of scholars about joint property has given birth to the opinion that joint property can be equated with shirkah, because the wife joint property can be equated with shirkah, because the wife can also be counted as a partner (partnership) who works, although the wife can also be counted as a partner (partnership) who works. (partnership) who work, although not participate in the work in the real sense